Polski Październik ’56 a lubelski Związek Bojowników o Wolność i Demokrację - Bednarski, Łukasz (Pamięć i Sprawiedliwość, 2012)
Polish October 1956 and the Lublin branch of ZBOWiD (Society of Fighters for Freedom and Democracy)The Lublin branch of ZBoWiD was established simultaneously with theveterans’ organisation ZBoWiD, in 1949. In the Stalinist period the activities of the Lublin branch boiled down to propaganda. Its functions were limited by members from PZPR (the Polish United Workers’ Party, PUWP), striving to eliminate the Society, as e.g. Grzegorz Wajskop.After 1956 the organisation accomplished a strong comeback, based uponformer AK (Home Army) soldiers. The catalyst of the organisation’s renewal after 1956 was the spontaneous voivodeship (provincial) convention staged by WW2 partisans of the Lublin region on 11 th November, 1956. As a result of elections held in individual local branches throughout the voivodeship, their managements were joined by mainly soldiers, former members of such underground organisations, as BCh (Peasant Battalions) and AK. They dominated the key positions in ZBoWiD, removing the representative of extreme leftist underground organisations (GL/AL, People’s Guard/People’s Army). At conventions numerously attended by partisans of the Lublin region, the Stalinist period (symbolised by Lavrentiy Beria) and the persecutions of those years were discussed, and harshly criticised by participants of the convention. AK/BCh soldiers maintained their influence in the Society until 1958. Subsequently to new elections to the Society’s authorities, strictly associated with the approaching 2 nd Congress of ZBoWiD (in 1959), AK and BCh members were pushed out of the Society’s authorities, former GL/AL soldiers (now members of PZPR) being selected to replace them. AK/BCh member again sufferedmarginalisation and discrimination from 1959 on, performing marginal, meaningless functions.The article presents how the events of one of the so-called Polish monthsimpacted the functions and rebirth of the Society in the post-Stalinist period; it is also an attempt to outline the political position achieved by AK soldiers in ZBoWiD after 1956.